Easy preparation, characterization and reactions of new 8‐chloro‐7‐formyl‐4‐oxo‐2‐phenyl‐4H‐pyrimido[1, 2‐a]pyrimidine‐3‐carbonitrile. (19th February 2021) - EL‐mahdy, Kamelia M.; Farouk, Osama
Abstract : 8‐Chloro‐7‐formyl‐4‐oxo‐2‐phenyl‐4 H ‐pyrimido[1, 2‐ a ]pyrimidine‐3‐carbonitrile (3 ) is constructed using N ‐(5‐cyano‐6‐oxo‐4‐phenyl‐1, 6‐dihydropyrimidin‐2‐yl) acetamide (2 ) via Vilsmeier‐Haack formylation reaction. Compound 3 reacted with 3‐(triethoxysilyl)propan‐1‐amine under different conditions. Condensation of pyrimidopyrimidine 3 with thiosemicarbazone derivative gave Schiff base 8, which upon treating with Vilsmeier‐Haack reagent afforded pyrazole carbothioamide 9 . Cyclocondensation of compound 3 with some binucleophiles namely thiocarbohyrazide, hydrazine carbodithioic acid, benzyl hydrazinecarbodithioate and/or 2‐thioxopyrimidinone was investigated. Structures of the new synthesized compounds were confirmed by their analytical and spectral data. Abstract :